The joint benefits of observed and unobserved punishment: Comment to unobserved punishment supports cooperation - Andreas Glöckner; Sebastian Kube; Andreas Nicklisch (Max Planck Institute for Research on Collective Goods, 2011)
Laboratory experiments by Fudenberg and Pathak (2010), and Vyrastekova, Funaki and Takeuch (2008) show that punishment is able to sustain cooperation in groups even when it is observed only in the end of the interaction sequence. Our results demonstrate that the real power of unobserved punishment is unleashed when combined with observable punishment. Providing both unobserved and observed punishment strongly enhances cooperation within groups - strikingly, even with less intense sanctioning. This surprising result underlines the importance of the coexistence of observed and unobserved sanctioning mechanisms in social dilemmas.
Keywords: H41; C92; H40; 330; Public Goods; Unobserved Punishment; Sanctioning Effectiveness; Öffentliches Gut; Nichtkooperatives Spiel; Strafe; Kooperation; Gefangenendilemma; Test